Application of Nitrogen and Phosphorus Fertilizers to the Vegetative Growth of Red Chilies (Capsicum Year L.) - Nurul Huda; Nurlina (Agricultural Science, 2025)
This study aims to determine the extent of the effect of Nitrogen and phosphorus on the vegetative growth of red chili plants. The research method was carried out at the Experimental Garden of the Faculty of Agriculture, Merdeka University, Surabaya. This study used a factorial Randomized Block Design (RAK) with two factors and three plant replications. The results showed a significant interaction between the combination of Nitrogen and Phosphorus treatments on Plant Height observations. The treatment of the correct (highest) Nitrogen fertilizer dose was shown by the N3 treatment and was significantly different from the N1 and N2 treatments on the parameters of plant height, number of leaves and number of branches. The treatment of the correct (highest) Phosphorus fertilizer dose was shown by the P2 treatment and was significantly different from the P1 treatment on the parameters of plant height, number of leaves and number of branches.